A Comparative Economic Analysis of Mash and Pelleted Feed in Broiler Production under Deep Litter Housing System - Gadzirayi, Christopher Tafara; Mutandwa, Edward; Chihiya, Jordan; Mlambo, Rhoda (International Journal of Poultry Science, 2006)
The study examined the economic effects of using mash and pelleted feed on Cobb 500 broilers. Two treatments, comprising 120 broilers were conducted under similar environmental conditions over a period of 4 months. Data on weight gain, feed quantities consumed, feed wastage as well variable costs such as feed and labour costs was collected using document analysis and direct observations. Analytical tools used included ANOVA, comparative gross margin analysis and t-tests. The study found out that there was no significant difference in terms of growth rate during the early stages of growth up to 32 days for birds fed on mash and those fed on pellets. However significant differences in growth rate were noted from 32 to 42 days. No significant difference was noted in the gross margins between pellet and mash fed birds. The study recommends that either mash or pelleted feed can be used depending on the farmer`s preferences.